Ta’śīru Niẓāmi al-Luġati fī Mahārati al-Kalām al-ʿArabī ladā Talāmīżi al Madrasati al-Mutawassiṭati - Sufandi; Ainul Yakin (KURAS Institute, 2023)
Discipline is something that can provide therapy through existing rules for students, especially in terms of developing language skills. From their activities, it is hoped that later they will feel motivated to continuously grow, learn to speak and be independent. Finally, there will be awareness of them, In this study, we want to describe whether there is an influence of language discipline on students' Arabic speaking skills at MTs. Nurulhuda Pakandangan Barat Kec. Bluto Kab. Sumenep and how much influence Language Discipline has on students' Arabic speaking skills at MTs. Nurulhuda Pakandangan Barat Kec. Bluto Kab. Sumenep. The research used correlational quantitative research with the number of students at MTs Nurulhuda Pandandang Kec. Bluto Kab. Sumenep 80 students. In an effort to obtain, explore and collect the data needed in the process of presenting and analyzing accurate data, the authors use questionnaires, tests, and documentation. The data analysis used in this study is the Product Moment statistical analysis technique. The results of the research can be concluded that there is an influence of language discipline on students' Arabic speaking skills at MTs. Nurulhuda Pakandangan Barat Kec. Bluto Kab. Sumenep. This can be proven by looking at the critical price table of r product moment with N = 80 with a significance level of 95% = 0.213 and a significance level of 99% = 0.278, it turns out that r work (0.636), is greater than the value of the critical price either at the significant level 95% and 99% and from the calculation results in it can also be concluded that the students' Arabic speaking skills at MTs. Nurulhuda Pakandangan Barat Kec. Bluto Kab. Sumenep is determined or influenced by language discipline by 40.45% while the remaining 59.55% is determined by other factors.